Centaurea debeauxii Gren. & Gordon (Asteraceae, Cardueae), an european species, new for Uruguay - Orfeo Crosa, O.; Bancheva, S. (Agrociencia Uruguay, 2006)
A new, exotic, naturalized, species of Asteraceae, Centaurea debeauxii, found in the Department of Montevideo, Uruguay, is described.